SCREENING POTATO GERMPLASM FOR STABLE RESISTANCE AGAINST LATE BLIGHT (PHYTOPHTHORA INFESTANS) - Srivastava, A K; Kumar, Vinod; Joseph, T A; Sharma, S; Bag, T K; Singh, B P (Potato Journal, 2013)
Fifty-three germplasm accessions of potato were screened at three locations viz., Kufri, Shillong and Ooty for late blight resistance from 2004 to 2008. Thirty-seven lines showed resistance against late blight at Kufri while seventeen and fifteen lines showed resistance at Shillong and Ooty, respectively. Eleven accessions showed resistance to late blight at two locations while twenty lines were resistant at only one location. The accessions CP1673, CP2011, CP2068, CP2132 and CP2333 showed resistance against late blight at all the locations along with desirable tuber characters and can be utilized as parents for transferring stable late blight resistance in varietal breeding programme.